Late‐interseismic state of a continental plate‐bounding fault: Petrophysical results from DFDP‐1 wireline logging and core analysis, Alpine Fault, New Zealand. (23rd September 2013) - Townend, J.; Sutherland, R.; Toy, V. G.; Eccles, J. D.; Boulton, C.; Cox, S. C.; McNamara, D.
<x xml:space="preserve">Abstract</x> [1] We present a geophysical characterization at 0.1–100 m scales of a major plate‐bounding continental fault in a late‐interseismic state. The Alpine Fault produces MW∼8 earthquakes every 200–400 years and last ruptured in 1717 AD. Wireline geophysical logs and rock cores extending from one side of the Alpine Fault to the other were acquired in two boreholes drilled in 2011 at Gaunt Creek during the first phase of the Deep Fault Drilling Project (DFDP‐1). These data document ambient conditions under which the next Alpine Fault earthquake will occur. Principal component analysis of the wireline logging data reveals that >80% of the variance is accounted for by electrical, acoustic, and natural gamma properties, and preliminary multivariate classification enables the lithologies of sections of missing core to be reconstructed from geophysical measurements. The fault zone exhibits systematic variations in properties consistent with common processes of progressive alteration and comminution near the principal slip zone, superimposed on different protolith compositions. Our observations imply that the fault zone has the opposite sense of elastic asymmetry at 0.1–100 m scales to that of the crustal‐scale orogen imaged by remote geophysical methods. On the basis of the fault‐zone scale asymmetry, the bimaterial interface model of preferred earthquake rupture directions implies a northeastward direction of preferred Alpine Fault rupture. On‐going characterization of the structural and hydraulic architecture of the Alpine Fault will improve our understanding of the relationship between in situ conditions, earthquake rupture processes, and the hazards posed by future earthquakes.